Overdose pattern and outcome in paracetamol‐induced acute severe hepatotoxicity - Craig, Darren G. N.; Bates, Caroline M.; Davidson, Janice S.; Martin, Kirsty G.; Hayes, Peter C.; Simpson, Kenneth J. (British journal of clinical pharmacology, 2011)
WHAT IS ALREADY KNOWN ABOUT THIS SUBJECT • Paracetamol hepatotoxicity is the commonest cause of acute liver failure (ALF) in the UK. • Conflicting data exist regarding the impact of overdose pattern upon subsequent mortality or need for emergency liver transplantation. WHAT THIS STUDY ADDS • Unintentional paracetamol overdose is independently associated with reduced survival compared with intentional overdose. • Unintentional paracetamol overdoses should be treated as high‐risk for the development of multiorgan failure, and should be considered for N‐acetyl cysteine treatment irrespective of admission serum paracetamol concentrations. • The King's College poor prognostic criteria have reduced sensitivity in unintentional overdose patients and alternative prognostic criteria may be required. AIMS Paracetamol (acetaminophen) hepatotoxicity is the commonest cause of acute liver failure (ALF) in the UK. Conflicting data regarding the outcomes of paracetamol‐induced ALF resulting from different overdose patterns are reported. METHODS Using prospectively defined criteria, we have analysed the impact of overdose pattern upon outcome in a cohort of 938 acute severe liver injury patients admitted to the Scottish Liver Transplantation Unit. RESULTS Between 1992 and 2008, 663 patients were admitted with paracetamol‐induced acute severe liver injury. Of these patients, 500 (75.4%) had taken an intentional paracetamol overdose, whilst 110 (16.6%) had taken an unintentional overdose. No clear overdose pattern could be determined in 53 (8.0%). Unintentional overdose patients were significantly older, more likely to abuse alcohol, and more commonly overdosed on compound narcotic/paracetamol analgesics compared with intentional overdose patients. Unintentional overdoses had significantly lower admission paracetamol and alanine aminotransferase concentrations compared with intentional overdoses. However, unintentional overdoses had greater organ dysfunction at admission, and subsequently higher mortality (unintentional 42/110 (38.2%), intentional 128/500 (25.6%), P < 0.001). The King's College poor prognostic criteria had reduced sensitivity in unintentional overdoses (77.8%, 95% confidence intervals (CI) 62.9, 88.8) compared with intentional overdoses (89.9%, 95% CI 83.4, 94.5). Unintentional overdose was independently predictive of death or liver transplantation on multivariate analysis (odds ratio 1.91 (95% CI 1.07, 3.43), P= 0.032). CONCLUSIONS Unintentional paracetamol overdose is associated with increased mortality compared with intentional paracetamol overdose, despite lower admission paracetamol concentrations. Alternative prognostic criteria may be required for unintentional paracetamol overdoses.